STUDY ON BASICITY IN DIRECT REDUCED IRON SMELTING - Nuryadi Saleh; Siti Rochani (Puslitbang tekMIRA, 2015)
Pig iron as raw material for steel production, can be prepared by smelting a Direct Reduced Iron (DRI)/sponge iron. The smelting process needs optimum conditions to obtain such a high recovery likes basicity, which measures the ratio of alkalinity or acidity by adding the exact quantity of flux (CaCO3) and quartz sand to input materials to generate the reduction process running well. In this study, smelting process was conducted using DRI sample mixed with varied flux (CaCO3), quartz sand and coal. Then a mixture was fed to a resistance furnace. The reduction process was carried out at a temperature of 1600°C, for 1-2 hour. Pig iron as product and slag were analyzed to obtain its chemical composition. Afterward, recovery products was calculated. The results showed that the best conditions in these experiments were achieved at 1.18 basicity with pig iron recovery was reached up to 95.79%, contented of 95.84% Fe, 3.52% C and 0.0024% SiO2. These data of this study can be used as reference of flux (limestone), quartz sand and carbon addition as input to resistance furnace in smelting process of sponge iron on a larger scale.